Beginning Database: A Practical Approach for Non-relational Database - Emran, Nurul Akmar (Penerbit Kolej Universiti Teknikal Malaysia Melaka, 2006)
Developing any applications that involve storage of data in a database requires application developer to carefully and precisely build design plans in order to produce high quality and useful product. There are many approaches that can be adopted in order to explain database design. Furthermore, database technology is rapidly developed and changing. As the result, the way to describe database design should be updated in order to reflect the current and latest database technology. The primary objective of this book is to equip the students with basic knowledge on how to design database for other types of data model like object-oriented and object-relational data model.